2011
DOI: 10.1113/jphysiol.2011.212043
|View full text |Cite
|
Sign up to set email alerts
|

Maternal dexamethasone and EEG hyperactivity in preterm fetal sheep

Abstract: Non-technical summary Long-acting glucocorticoids such as dexamethasone are commonly given to women at risk of preterm labour. While they significantly improve survival of the prematurely born infant, their effects on preterm brain activity is surprisingly unclear. We found that, in sheep, a conventional clinical course of maternal dexamethasone treatment was associated with dramatic, evolving low-frequency hyperactivity of the fetal EEG. This activity reflected a striking shift to less-frequent but higher amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
44
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 63 publications
5
44
0
Order By: Relevance
“…Recent evidence suggests that maternal treatment with dexamethasone in doses similar to those in our study was associated with increased epileptiform activity, consistent with electrographic and clinical seizures on fetal cortical EEG recordings, and with later changes in the fetal EEG indicative of increased maturation of fetal sleep architecture (Davidson et al, 2011). The increases in cerebral cortical connexin-36 and -43 that we detected potentially reflect increases in neuronal and astrocytic gap junction channels that could facilitate increased cell-to-cell electrical communication (Eugenin et al, 2012) and have allowed for the recently reported increased epileptiform activity observed after maternal dexamethasone treatment (Davidson et al, 2011).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Recent evidence suggests that maternal treatment with dexamethasone in doses similar to those in our study was associated with increased epileptiform activity, consistent with electrographic and clinical seizures on fetal cortical EEG recordings, and with later changes in the fetal EEG indicative of increased maturation of fetal sleep architecture (Davidson et al, 2011). The increases in cerebral cortical connexin-36 and -43 that we detected potentially reflect increases in neuronal and astrocytic gap junction channels that could facilitate increased cell-to-cell electrical communication (Eugenin et al, 2012) and have allowed for the recently reported increased epileptiform activity observed after maternal dexamethasone treatment (Davidson et al, 2011).…”
Section: Discussionsupporting
confidence: 85%
“…The increases in cerebral cortical connexin-36 and -43 that we detected potentially reflect increases in neuronal and astrocytic gap junction channels that could facilitate increased cell-to-cell electrical communication (Eugenin et al, 2012) and have allowed for the recently reported increased epileptiform activity observed after maternal dexamethasone treatment (Davidson et al, 2011). …”
Section: Discussionmentioning
confidence: 72%
“…Brain development at this age is broadly consistent with 28 to 32 wk in humans, before the development of cortical myelination (14). The fetal EEG at this age is consistent with that of the preterm human infant, with discontinuous mixed-frequency activity with periods of quiescence (the so called interburst interval) alternating with periods of high-amplitude slowwave activity (15,16).…”
mentioning
confidence: 52%
“…Total EEG power (µV 2 ) was calculated from the intensity spectra. Quantitative EEG measurements for each waveform were performed to quantify power in the Δ (0-3.9 Hz), θ (4-7.9 Hz), α (8-12.9 Hz), and β (13)(14)(15)(16)(17)(18)(19)(20)(21)(22) bands. This involved calculating power spectra (by fast Fourier transform) of the EEG on sequential epochs, using a 10 s Hanning window to minimize spectral leakage.…”
Section: Recordingsmentioning
confidence: 99%
“…Tapered neonatal dexamethasone in rats alters cortical spreading depression velocity (an evoked propagating wave) in mature animals, but not cortical potentiation [83]. Whilst maternal exposure to dexamethasone in fetal sheep produces changes in EEG power bands lasting at least several days in utero [84], however it is unknown if these changes extend into adulthood, or for more than a few days. Therefore, perinatal glucocorticoids may have effects on brain function, but they do not appear to enduring changes specific to neuropsychiatric traits in electrophysiology measures of brain function.…”
Section: Discussionmentioning
confidence: 99%